Inheritance of resistance to the Papaya ringspot virus-watermelon strain (PRSV-W) from watermelon accession 'PI 595201' - Azevedo,Sebastião Márcio de (2012)
Two watermelon genotypes were used as parental in crosses designed to study the inheritance of resistance to PRSV-W: the cultivar Crimson Sweet (susceptible) and the accession 'PI 595201'(resistant). Plants of the generations P1, P2, F1, F2, BC11 e BC12 were inoculated with a Brazilian isolate of PRSV-W and were evaluated by recording symptoms. Genetic and phenotypic parameters of PRSV-W resistance were estimated and tests based on hypothesis of monogenic inheritance and maximum likelihood methods were performed. The additive component [a] of resistance was higher than the non-additive [d]. The estimates of the broad-sense heritability (0.80) and of narrow-sense heritability (0.67) indicated that the genetic variance was greater than the environmental, allowing higher genetic gains in selecting more resistant plants in segregating populations. The inheritance is more complex than a typical monogenic inheritance. The importance of the additive genetic effects in the expression of resistance to PRSV-W was evidenced.